Hacking for humanity. - Goldstein, H.
He brings the hacker ethic and Internet access to the far corners of the globe. He attained geek immortality by coinventing the Sol-Ã?Â20 personal computer in the mid-Ã?Â1970s. He was a key member of the legendary Homebrew Computer Club and a recurring character in Steven Levy's 1984 book, Hackers. So you'd think that nowadays Bob Marsh might be tripping the light fantastic like fellow personal-Ã?Âcomputer pioneer Steve Wozniak, or at least kicking back and enjoying retirement.